Managing Climate Change: The Role of Religion in Selected Church Sponsored Schools in Tigania West Sub-County - Fridah Kathambi, (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
This study aimed at investigating the role of religion in mitigating climate change in selected church sponsored schools in Tigania West Sub-County. Religion plays a crucial role in shaping the beliefs, values, and behaviors of individuals towards their environment. However, the role of church sponsored schools in training future community leaders is not well documented. The study was conducted in selected church sponsored schools in Tigania West Sub-County in Meru County. It adopted a descriptive survey design where the principals, teachers and sponsors were targeted. Stratified random sampling technique was adopted where questionnaires and interviews were used to collect data. The study showed that the church played a great role in instilling moral values on students while little is known about their role in climate change mitigation. Therefore, this study highlights a potential gap in the education. The findings of this study suggest that there is a need for religious institutions to rethink their educational priorities and consider incorporating teachings on climate change mitigation into their curriculum. This can play a vital role in shaping the attitudes and behaviors of students towards environmental stewardship and fostering a sense of responsibility towards environment. Religion can play a crucial role in addressing climate change by promoting stewardship, inspiring action and advocacy, and providing a moral and ethical framework for decision-making. By integrating religious teachings and values into the school culture, can result to a positive impact in the society. The role of religion is significant in fostering environmental awareness, education, and action towards mitigating climate change. Thus, schools have the potential to shape the attitudes and behaviors of their students towards a more sustainable and environmentally conscious future. Climate change education could be integrated into the school curriculum; promote sustainable practices within the school community, such as reducing waste, conserving energy, and promoting eco-friendly transportation options; engage the school community in environmental initiatives such as workshops, and campaigns focused on environmental conservation and climate action; partner with environmental organizations and experts and encourage reflection on environmental stewardship.